Into the ice : the Northwest Passage, the Polar Sun, and a 175-year-old mystery - Synnott, Mark (Dutton, an imprint of Penguin Random House LLC, 2025)
"Only a few hundred vessels have ever transited the Northwest Passage, and substantially fewer have done so in a fiberglass-hulled boat like Polar Sun. But Mark was determined to return to the Arctic, where he cut his teeth as a young climber, and in the process investigate one of the great mysteries of exploration: What really happened to Sir John Franklin and his entire 128-man crew, which disappeared into these ice-strewn waters 175 years ago? In this pulse-pounding travelogue, Mark Synnott paints a vivid portrait of the Arctic, which is currently warming twice as fast as any other part of our planet. He weaves its history and people into the first-person account of his epic journey through the Northwest Passage, searching for Franklin's tomb along the way--all while trying to avoid a similar fate. In Into the Ice, Mark and his crew race against time and treacherous storms in search of answers to the greatest mystery of all time: What is it that drives someone to risk it all in the name of exploration?"--